Conditional over-expression of heme-oxygenase 1 in myelomonocytic cells reduces hypertension and vascular inflammation. (3rd October 2022) - Aluia, M; Kuntic, M; Jurk, K; Daiber, A; Reinhardt, C; Lagrange, J; Wenzel, P
Abstract: Background: Arterial hypertension is one of the most important modifiable risk factors for all-cause morbidity and mortality worldwide. Angiotensin II (Ang II) plays a pathogenic role in the development of hypertension, vascular dysfunction, inflammation and tissue damage. In the context of hypertension, heme-oxygenase 1 (HO-1) gene expression is upregulated as an antioxidant defense system in response to AngII through its action on heme catabolism, which generates carbon monoxide (CO), ferritin and biliverdin, which is reduced to bilirubin by biliverdin reductase A (BLVRA). Previous studies have shown the important role of HO-1 in the maturation and migration of immune cells. Myeloid HO-1 modulates macrophage polarization and protects against ischemia-reperfusion damage. However, the role of myeloid cell specific HO-1 in the detrimental effects of AngII induced vascular dysfunction has not yet been explored. Objectives: To investigate the potential vascular protection of myeloid cell specific overexpression of HO-1 in AngII-induced arterial hypertension. Methods: Hypertension was induced in 8–13 weeks old male mice with selective over-expression of HO-1 (HO-1indLysMcre) in myelomonocytic cells versus LysMCre/wt by AngII infusion (1mg/kg/d). Blood pressure was recorded by tail-cuff. Bilirubin levels were quantified in plasma by High Performance Liquid Chromatography (HPLC). The quantification of adherent and rolling leukocytes in carotid arteries was detected by intravital video microscopy (IVM). Endogenuos Thrombin potential (ETP) was measured in platelet rich plasma (PRP) and platelets poor plasma (PPP) by Calibrated Automated Thrombogram (CAT) assay. Endothelium-dependent vasodilation was assessed in isolated aortic rings by concentration-relaxation curves in response to acetylcholine (ACh). Results: AngII-infused HO-1indLysMcre had decreased blood pressure values and improved endothelial function as compared to LysMcre controls. IVM revealed reduced leukocyte rolling and adhesion to the vascular endothelium in AngII infused HO-1indLysMcre mice compared to controls, paralleled by reduced expression of NOX-2 mediated oxidative stress and vascular inflammation in AngII-induced arterial hypertension by decreasing VCAM-1, CCR2 and MCP-1 expression. mRNA analysis revealed an increased expression of BLVRA in liver, spleen, heart and aortic tissues in response to AngII, which was higher in HO-1indLysMcre mice than in controls. By CAT assay we registered a decrease ETP in PPP and PRP in HO-1ind mice infused with AngII compatible with less abundance of inflammatory platelets, potentially regulated by BLVRA activity. This was supported by increased in bilirubin levels in response to AngII, which was higher in HO-1indLysMcre mice than in controls. Conclusion: Myeloid cell specific overexpression of HO-1 confers anti-inflammatory protection to the vasculature in AngII induced hypertension. This effect is, at least in part, mediated by BLVRA. Funding Acknowledgement: Type of funding sources: None.